“Todavía es posible soñar”: Teoría apreciativa y Comunicación Organizacional - Varona, Federico (Organicom, 2004)
This article describes the nature of Appreciative Theory, its characteristics and the four steps of the appreciative intervention. Describes the different modalities for conducting an intervention in the organizational environment and the conditions for success. The author also discusses the major challenges of the Theory, as well as the power and characteristics of positive language and thinking. The article ends with an exercise on how to apply this theory in organizations.